Unique hyaluronan structure of expanded oocyte-cumulus extracellular matrix in ovarian follicles - Nagyová, Eva; Mlynarčíková, Alžbeta; Němcová, Lucie; Scsuková, Soňa (Endocrine regulations, 2024)
In preovulatory follicles, after the endogenous gonadotropin surge, the oocyte-cumulus complexes (OCCs) produce hyaluronan (HA) in a process called “cumulus expansion”. During this process, the heavy chains (HCs) of the serum-derived inter-alpha-trypsin inhibitor (IαI) family bind covalently to synthesized HA and form a unique structure of the expanded cumulus HA-rich extracellular matrix. Understanding the biochemical mechanism of the covalent linkage between HA and the HCs of the IαI family is one of the most significant discoveries in reproductive biology, since it explains basis of the cumulus expansion process running in parallel with the oocyte maturation, both essential for ovulation. Two recent studies have supported the above-mentioned findings: in the first, seven components of the extracellular matrix were detected by proteomic, evolutionary, and experimental analyses, and in the second, the essential role of serum in the process of cumulus expansion in vitro was confirmed. We have previously demonstrated the formation of unique structure of the covalent linkage of HA to HCs of IαI in the expanded gonadotropin-stimulated OCC, as well as interactions with several proteins produced by the cumulus cells: tumor necrosis factor-alpha-induced protein 6, pentraxin 3, and versican. Importantly, deletion of these genes in the mice produces female infertility due to defects in the oocyte-cumulus structure.